2018
DOI: 10.1111/ijfs.14031
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Phaseolus lunatus peptides release from maltodextrin/gum arabic microcapsules obtained by spray drying after simulated gastrointestinal digestion

Abstract: Bioactive peptides can be protected from the gastrointestinal environment by microencapsulation. The aim was to assess the effect of simulated gastrointestinal digestion on bioactive properties of P. lunatus peptides (ACE‐I, α‐glucosidase, α‐amylase, and dipeptidyl peptidase‐IV inhibition) microencapsulated by spray drying using maltodextrin/gun arabic in optimal formula. Microcapsules were formulated using a 22 factorial design. The simultaneous effect of P. lunatus hydrolysate (4 and 10 g 100 g−1) and propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 30 publications
1
27
0
1
Order By: Relevance
“…Maltodextrin, starch, gum arabic, pectin and chitosan are the polysaccharides most studied as encapsulating agents and delivery systems, due to their abundance in nature and structural stability (Fathi et al ., ). Recently, the encapsulation of peptides obtained from different protein sources with maltodextrin and gum arabic blend by spray drying has been reported (Yang et al ., ; Rao et al ., ; Cian et al ., ). Even though carrageenans and sulphated polysaccharide extracted from red algae are extensively used in the food industry as gelling agent, stabilizers and texture enhancers (Cian et al ., ), they have not been studied as encapsulating agents (Papoutsis et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maltodextrin, starch, gum arabic, pectin and chitosan are the polysaccharides most studied as encapsulating agents and delivery systems, due to their abundance in nature and structural stability (Fathi et al ., ). Recently, the encapsulation of peptides obtained from different protein sources with maltodextrin and gum arabic blend by spray drying has been reported (Yang et al ., ; Rao et al ., ; Cian et al ., ). Even though carrageenans and sulphated polysaccharide extracted from red algae are extensively used in the food industry as gelling agent, stabilizers and texture enhancers (Cian et al ., ), they have not been studied as encapsulating agents (Papoutsis et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, several studies have demonstrated that most bioactive peptides containing more than 2-3 amino acid residues do not withstand simulated gastrointestinal digestion (Mohan et al, 2015), losing their bio-functional properties (De Koker et al, 2011). An alternative to protect them inside the gastrointestinal tract is by spray drying microencapsulation using different biopolymers (Cian et al, 2019). This technology produces a continuous matrix containing the active substances (Nesterenko et al, 2013), enhancing the bioaccessibility of food-derived bioactive peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, chitosan–TPP combinations under optimized conditions have been described as good peptides entrapment systems with controlled properties [ 237 ]. Maltodextrin is other commonly used polysaccharide-based carrier, alone or in combination with Arabic gum to retain the biological activity of casein [ 252 ], flaxseed protein [ 239 , 241 ], and Phaseolus lunatus protein [ 242 ] hydrolyzates.…”
Section: Bioavailability Of Food Peptidesmentioning
confidence: 99%
“…There are many encapsulating agents used in food industry. Maltodextrins (MDX) are one of the most utilized agents because they have high water solubility, low viscosity at high solid concentrations, and low cost (Šturm et al, 2019;Cian et al, 2018). Gum Arabic (GA) is another type of encapsulating agent also used because it has a good emulsifying capacity and presents low viscosity in aqueous solutions (Šturm et al, 2019).…”
Section: Spray Drying Microencapsulation Of Purple Cactus Pear (Opuntmentioning
confidence: 99%